A pseudo - panel approach to estimating dynamic effects of road infrastructure on firm performance in a developing country context - Barzin,S; D'Costa,S; Graham,DJ (Regional Science and Urban Economics, 2018)
To overcome the absence of true firm-level data, we provide evidence that the use of pseudo-panels based on aggregated data can correctly identify production function parameters. We construct a pseudo-panel of Colombian manufacturing firms for the years of 2000–2009 to study the effects of transportation infrastructure on firm performance in a developing country and find elasticities of output with respect to road infrastructure ranging from 0.13 to 0.15 per cent. This confirms that roads are important for private output growth and, as our results are larger than those reported in the literature for developed countries, that transportation infrastructure is relatively more important for the economy of developing countries. We also identify a one-year time lag with which firms' outputs react to road stock changes. This could be indicative of firms requiring time to adjust their production to road changes. We furthermore identify that the effect of road infrastructure is particularly large for heavy manufacturing industries. Moreover, we investigate the regional heterogeneity of the role of transportation infrastructure for firms' output growth. Our results are robust to different econometric concerns. We additionally provide Monte Carlo simulations to support the validity of pseudo-panels in the context of firm-level data.